INFLUENCING INTERNATIONAL STUDENTS’ LEARNING READINESS AND THEIR PERFORMANCE IN SELECTED CHINESE UNIVERSITIES - Jin, Liu; Ghani, Muhammad Faizal A. (EARR (Educational Administration Research and Review), 2023)
Local research on  international students at Chinese universities is often related to the challenges that they encounter. The research on the impact of such challenges on their academic achievement, such as their learning readiness is still lacking. Therefore, this study aims to analyze the influence of international student learning readiness on their achievement. To address the research objective, a quantitative research involving 275 selected international students with origins in Central Asia, South Asia, Southeast Asia, the Middle East and North Africa and Europe was carried out. Questionnaires were distributed and the data were analyzed using descriptive statistical methods such as mean and percent, and a  inferential statistical method (logistic regression). This study found that international students’ learning readiness influenced their achievement in the aspects of content knowledge, cognitive skills, study skills and strategies, and habits of success with p0.05. The finding is available for stakeholders, especially researchers, to carry out further research in identifying the effectiveness of their learning readiness to overcome the challenges that were found by previous researchers.